The Effectiveness of Ethanol Extract Chayote (Sechium Edule (Jacq.) Swartz) Fraction and Juice on Pancreatic β-Cell Diameter of Male White Rats Wistar Strain with Type 2 Diabetes Mellitus - Hutagalung, Sanggam Bangun; Siahaan, Jekson Martiar; Silitonga, Hendrika Andriana (Indonesian Journal of Medicine, 2021)
Background: Diabetes Mellitus is characterrized by metabolic disturbances due to prolonged hyperglycemia, causing oxidative stress, which destroys pancreatic β cells. Adjuvant therapy that has antihyperglycemic effectiveness and is required to improve the diameter of pancreatic beta cells, one of which comes from Sechium edule (Jacq.) Swartz has potential as an antihyperglycemic, antioxidant, antiapoptosis, cardioprotective, insulin resistance. This study aimed to examine the effectiveness of ethanol extract, Chayote (Sechium Edule (Jacq.) Swartz) fraction, and juice on the pancreatic β-cell diameter of white male rats Wistar strain with type 2 diabetes mellitus.Subjects and Method: This was a randomized controlled trial. Sample was Rattus novergius sp. 54 tails. The dependent variable was the diameter of the pancreatic β cells. The independent variables were ethanol extract, Sechium edule (Jacq.) Swartz fraction and juice, at a dose of 50 mg/kg BW, 100 mg/ kg BW, 150 mg/kg BW. The data were analyzed by the ANOVA test.Results: The group of mice induced by Streptozotocin 50 mg/kg BW + nicotinamide (120 mg/ kg BW) + HFD and obtained ethanol extract of chayote fruit 150 mg/ kg BW, orally, had the highest pancreatic β cell diameter compared to the other groups (Mean= 284.03; SD= 5.15).Conclusion: Sechium edule (Jacq.) Swartz has potential as an anti-apoptosis that can inhibit pancreatic β cell damageKeywords: pancreatic β cells, anti-apoptosisCorrespondence: Sanggam Bangun Hutagalung. Department of Anatomical Pathology, Faculty of Medicine, Universitas Methodist Indonesia, Medan. Jl. Setia Budi Pasar II Tj. Sari, Medan 20132, North Sumatera. Email: sanggam1973@gmail.com.Indonesian Journal of Medicine (2021), 06(03): 239-245https://doi.org/10.26911/theijmed.2021.06.03.01